Recognition of prior learning : an introduction - Benton, Nena, 1940- (Wellington, N.Z. : New Zealand Council for Educational Research, 1995)
What is experiential learning? The RPL philosophy. The international context. The New Zealand context. Social justice issues. Goals, benefits and outcomes. Roles and responsibilities...
Keywords: Education; Higher education; Experiential learning; Experimental methods; College credits; College credits -- Outside work; College credits -- New Zealand -- Outside work; School credits; Experiential learning; Experiential learning -- New Zealand; Education, Higher -- New Zealand; Education -- New Zealand -- Experimental methods